Corporate Taxpayer Satisfaction and Compliance Analysis at Pratama Dumai Tax Office: Review of the Service System - Teddy Chandra; Evelyn Wijaya; Adi Suryadiningrat; Stefani Chandra; Jennifer Chandra (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
The improvement of services to corporate taxpayers is expected to increase the satisfaction of corporate taxpayers so it is expected to increase compliance in the taxation sector. The new paradigm that places government officials as servants of the state and society must be prioritized to improve the performance of public services. The purpose of the study was to determine the direct effect of the Service Quality variable on the Satisfaction and Compliance of Corporate Taxpayers. The population in this study were corporate taxpayers registered at Pratama Dumai Tax Office, which amounted to five thousand and thirty-seven taxpayers. To minimize the incompleteness of the data, in this study, a questionnaire will be distributed to ninety-eight respondents. Data analysis in this study used descriptive analysis and Partial least squares (PLS). The results of the analysis of service quality affect corporate taxpayer satisfaction, service quality affects corporate taxpayer compliance and taxpayer satisfaction affects corporate taxpayer compliance.